To find the antiderivative of the given function, we'll
have to determine the indefinite integral.
Int sqrt(1+sqrt
x) dx
We'll substitute 1 + sqrt x =
t
We'll differentiate both
sides:
dx/2sqrt x = dt
dx = 2
sqrt x*dt
But sqrt x = t -
1
dx = 2(t - 1)dt
We'll
re-write the integral in t:
Int sqrt t*2(t - 1)dt = 2Int
sqrt t^3 dt - 2 Int sqrt t dt
Int sqrt t*2(t - 1)dt =
2*t^(3/2 + 1)/(3/2 + 1) - 2*t^(1/2 + 1)/(1/2 + 1) + C
Int
sqrt t*2(t - 1)dt = 4t^(5/2)/5 - 4t^(3/2)/3 + C
Int sqrt
t*2(t - 1)dt = 4t^(3/2)( t/5 - 1/3) +
C
Int sqrt(1+sqrt x)dx = 4(1 + sqrt
x)^(3/2)[(1 + sqrt x)/5 - 1/3] + C
No comments:
Post a Comment